2010
DOI: 10.1021/la102026h
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Controlled Adsorption of Fc-Functionalized Polymers on β-CD-Modified Self-Assembled Monolayers

Abstract: This work presents an in situ study of the adsorption/desorption behavior of ferrocene(Fc)-functionalized linear polymers on a gold surface covered with beta-cyclodextrin(beta-CD)-modified self-assembled monolayers (SAMs). The characterization of binary SAMs obtained with HS-(CH(2))(11)-EG(6)-N(3) and HS-(CH(2))(11)-EG(4)-OH (EG, ethylene glycol) was performed using a quartz crystal microbalance with dissipation monitoring (QCM-D), cyclic voltammetry, and contact angle measurements. The functionalization of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 51 publications
4
74
0
Order By: Relevance
“…2 shows that the gold surfaces, which exhibited an initial contact angle of 75 ± 2°, became more hydrophilic after the formation of the pegylated SAM. As expected, the contact angles obtained for the mixed SAMs were intermediate between those of the pure monolayers of each single component (23), and surfaces became more hydrophobic after their click functionalization with hydrophobic guests. Remarkably, the evolution of the contact angles measured after immobilization of adamantane followed exactly the same trend as that obtained for SAM-Fc ( Fig.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…2 shows that the gold surfaces, which exhibited an initial contact angle of 75 ± 2°, became more hydrophilic after the formation of the pegylated SAM. As expected, the contact angles obtained for the mixed SAMs were intermediate between those of the pure monolayers of each single component (23), and surfaces became more hydrophobic after their click functionalization with hydrophobic guests. Remarkably, the evolution of the contact angles measured after immobilization of adamantane followed exactly the same trend as that obtained for SAM-Fc ( Fig.…”
Section: Resultssupporting
confidence: 73%
“…1C). To produce ferrocene-terminated SAMs (SAM-Fc), we subsequently attached ferrocene using an azidealkyne click reaction (16,23). The surface density of ferrocene (Γ Fc ; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDs were introduced by using click chemistry on preformed SAMs on gold surface; they showed the association and dissociation of ferrocene polymers into CD during the redox process. [69] In parallel, Kang et al reported the binding of a cyclodextrin polymer onto ferrocene-functionalized SAMs on gold electrode. Kang et al carried out atom-transfer radical polymerization (ATRP) on the surface of the gold electrode.…”
Section: Surface Adsorptionmentioning
confidence: 99%
“…Cyclodextrins (CDs) are a class of cyclic oligosaccharides which are widely used for their ability to form inclusion complexes with a large range of substrate molecules [25]. One of the most investigated pairs, β-CD and ferrocene (Fc) has been employed in electroactive macromolecular adhesion with strong binding ability [27,28], involving linear polymers [30,31], dendrimers [32] and nanotubes [33], etc. Furthermore, the host-guest interaction is usually reversible and depending on the redox state of ferrocene [25,27].…”
Section: Introductionmentioning
confidence: 99%